On coprimely structured rings - (:unkn) unknown (My University, 2016)
0

In this paper, we define coprimely structured rings, which are the generalization of strongly 0-dimensional rings. Furthermore, we investigate coprimely structured rings and give some relations between other rings such as Artinian rings, strongly 0-dimensional rings, and h-local domains.
Keywords: Matematik